Current Smoking has a Detrimental Effect on Survival for Epidermal Growth Factor Receptor (EGFR) and Anaplastic Lymphoma Kinase (ALK) negative Advanced non-squamous Non-small Cell Lung Cancer (NSCLC) Patients Treated with Pemetrexed Continuation Maintenance - Lin, Liping (J Cancer, 2018)
Objectives: The aim of this study is to investigate the predictive value of smoking history on treatment outcomes of pemetrexed continuation maintenance therapy in advanced non-squamous NSCLC patients without EGFR mutations and ALK rearrangements. Methods: 71 consecutive EGFR and ALK negative advanced non-squamous NSCLC patients who had received pemetrexed continuation maintenance therapy at least two cycles were retrospectively analyzed in our single center. The enrolled patients were categorized into two groups as never-/former light smokers and current smokers according to their smoking history. Results: In the 71 non-squamous NSCLC patients, 30 (42.3%) were never-/former light smokers and 41 (57.7%) were current smokers. The objective response rate (ORR) of never-/former light smokers was significantly higher than that of current smokers (26.7% vs. 7.3%, p = 0.026). Never-/former light smokers showed significantly longer progression free survival (PFS) (6.6 [95% CI 5.3-7.9] months vs. 5.1 [95% CI 3.5-6.7] months; HR: 0.557, 95% CI 0.339-0.915, p = 0.021) and overall survival (OS) (17.3 [95% CI 14.4-20.2] months vs. 15.7 [95% CI 12.0-19.4] months; HR: 0.578, 95% CI 0.338-0.986, p = 0.044) than current smokers. Multivariate analysis identified smoking history was an independent predictive factor for PFS and OS. Conclusions: Current smoking is an independent negative predictive factor of outcomes for pemetrexed continuation maintenance therapy in advanced non-squamous NSCLC patients without EGFR mutations and ALK rearrangements.